A clinical review of early outcomes from contemporary flow modulation versus open, fenestrated and branch technologies in the management of thoracoabdominal aortic aneurysm. (April 2018) - Sultan, Sherif; Kavanagh, Edel P; Diethrich, Edward; Costache, Victor; Sultan, Mohamed; Jordan, Fionnuala; Hynes, Niamh
Traditional therapeutic options for complex thoracoabdominal aneurysm include open repair, hybrid repair or endovascular repair (involving fenestrated or branched endografts). The Streamliner Multilayer Flow Modulator has been available for treatment of thoracoabdominal aneurysms since 2010. Its design permits blood flow to perfuse through the mesh in a modus that preserves collateral branch patency, while modulating turbulent to laminar flow within the device. The flow then stagnates over time within the surrounding aneurysm sac. Significant complications, including paraplegia, renal failure and cerebrovascular accident, are much lower with Streamliner Multilayer Flow Modulator treatment. Application of the Streamliner Multilayer Flow Modulator to complex aortic pathologies presents a novel solution to an, as of yet, unmet clinical need, and has resulted in promising clinical outcomes when compared to existing solutions. The Streamliner Multilayer Flow Modulator offers potential for treatment of thoracoabdominal aortic pathologies in patients and is not just confined to those with complexity that dictates no other management options. While current literature illustrates that there is a decreased risk of mortality and associated complications when this new disruptive technology is utilised, there is still a need for prospective, long-term clinical trials, as well as comparative trials to accurately assess outcomes of Streamliner Multilayer Flow Modulator treatment that are both precise and reproducible. This article is a review of current clinical literature regarding contemporary flow modulating technology compared with open, branched and fenestrated managements, presenting early outcomes.